Health-Promoting Properties of Pectin-Polyphenol Complex Extracted from Olive Oil By-Product Alperujo: Antioxidant, Antiproliferative, and Anti-Inflammatory Activities - Alejandra Bermúdez-Oria; María Luisa Castejón; Fátima Rubio-Senent; Guillermo Rodríguez-Gutiérrez; Juan Fernández-Bolaños (MDPI AG, 2024)
This research explores the health-promoting properties of the pectin-polyphenol complex extracted from alperujo, a by-product of olive oil production. This study investigates the chemical composition and antioxidant activity of the extracts, revealing their high antioxidant activity in vitro. Cell viability assays conducted on colon carcinoma cells (Caco-2) demonstrate the inhibitory effect of the extracts on cell proliferation. However, the extracts do not affect the viability of differentiated Caco-2 cells, suggesting a selective antiproliferative action. Additionally, the extracts reduce intracellular reactive oxygen species (ROS) and nitrite (NO) production in LPS-stimulated murine peritoneal macrophages. Furthermore, the extracts exhibit anti-inflammatory effects by downregulating the secretion of pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in these macrophages. These findings highlight the potential of pectin-polyphenol complexes as functional ingredients with significant health benefits, demonstrating antioxidant, antiproliferative, and anti-inflammatory properties.